2018
DOI: 10.1093/jat/bky021
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Quantitative LC–MS-MS Assay for Codeine, Morphine, 6-Acetylmorphine, Hydrocodone, Hydromorphone, Oxycodone and Oxymorphone in Neat Oral Fluid

Abstract: Recent advances in analytical capabilities allowing for the identification and quantification of drugs and metabolites in small volumes at low concentrations have made oral fluid a viable matrix for drug testing. Oral fluid is an attractive matrix option due to its relative ease of collection, reduced privacy concerns for observed collections and difficulty to adulterate. The work presented here details the development and validation of a liquid chromatography tandem mass spectrometry (LC-MS-MS) method for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Langel et al [46] reported good stability at − 18 °C for morphine, codeine, diazepam and alprazolam for 28 days, using Quantisal™ as collector device. Grabenauer et al [47] similarly noted that for 6-monoacetylmorphine, codeine, hydromorphone, oxymorphone and morphine were stable in the neat oral fluid at both refrigerator (8 °C) and freezer (− 20 °C) temperatures for up to 4 weeks. Hydrocodone was reported by Grabenauer et al [47] to be unstable under refrigerator conditions for over 7 days, but our results R. Temp room temperature, F/T cycles freeze/thaw cycles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Langel et al [46] reported good stability at − 18 °C for morphine, codeine, diazepam and alprazolam for 28 days, using Quantisal™ as collector device. Grabenauer et al [47] similarly noted that for 6-monoacetylmorphine, codeine, hydromorphone, oxymorphone and morphine were stable in the neat oral fluid at both refrigerator (8 °C) and freezer (− 20 °C) temperatures for up to 4 weeks. Hydrocodone was reported by Grabenauer et al [47] to be unstable under refrigerator conditions for over 7 days, but our results R. Temp room temperature, F/T cycles freeze/thaw cycles.…”
Section: Discussionmentioning
confidence: 98%
“…Grabenauer et al [47] similarly noted that for 6-monoacetylmorphine, codeine, hydromorphone, oxymorphone and morphine were stable in the neat oral fluid at both refrigerator (8 °C) and freezer (− 20 °C) temperatures for up to 4 weeks. Hydrocodone was reported by Grabenauer et al [47] to be unstable under refrigerator conditions for over 7 days, but our results R. Temp room temperature, F/T cycles freeze/thaw cycles. For LQC and HQC see Table 1 Table 4 (continued) 6), which assured Quantisal™ buffer efficiency in compound stability.…”
Section: Discussionmentioning
confidence: 98%
“…HPLC has been reported to simultaneously detect several opioid drugs with similar structures such as heroin, morphine, and codeine in the sample due to its ability to separate the drugs [73]. Various detectors have been coupled with HPLC including optical detectors (e.g., photomultiplier tube (PMT) and photodiode array (PDA)) [76,77] and mass spectrometry (MS) [78][79][80][81][82].…”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…Hu et al reported LC/MS-MS combined with liquid-liquid extraction for the simultaneous determination of codeine, ephedrine, guaiphenesin, and chlorpheniramine in beagle dog plasma, achieving a limit of quantification of 0.08 ng/mL [79]. Another sample preparation for LC/MS-MS analysis was reported using solid-phase extraction to extract codeine, morphine, 6-acetylmorphine, hydrocodone, hydromorphone, oxycodone, and oxymorphone from neat oral fluid [80]. Furthermore, Sproll et al used a cold extraction method using methanol containing 0.1% acetic acid to extract opiate alkaloids from poppy seeds [81].…”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…However, oral fluid has a small detection window when compared to other biological specimens [11][12][13][14][15]. Numerous methods have been published for the determination and identification of COC, opiates, and their metabolites in oral fluid, using different extraction techniques, such as the classical solid-phase extraction (SPE) [16][17][18][19][20][21], liquid-liquid extraction (LLE) [22,23], and protein precipitation (PP) [24][25][26][27] approaches, or more recently miniaturized techniques, for instance microextraction by packed sorbent (MEPS) [28,29]. Concerning chromatographic methods, the most commonly used is liquid chromatography (LC) coupled to tandem mass spectrometry (MS/MS) [13,[17][18][19][20][23][24][25][26][30][31][32][33], but gas chromatography coupled to mass spectrometry (GC-MS) [13,16,22,32] and ultra-high-performance liquid chromatography (UHPLC) coupled to MS/MS have also been reported [13,21,27,28,32,[34][35]…”
Section: Introductionmentioning
confidence: 99%